Practical motion control with acceleration reference for precision motion - new NCTF control and its application to non-contact mechanism - Chong, Shin Horng (Elsevier, 2011)
This paper presents an improved practical controller for enhancing precision motion performance. For practical use, high motion control performance and ease of controller design are desired. A nominal characteristic trajectory following control (NCTF control) has been studied to satisfy the desired response. The NCTF controller consists of a nominal characteristic trajectory (NCT) which is the reference motion of control system and a compensator which makes the motion of the controlled object to follow the NCT. The NCT is easily determined from experimental open-loop time responses of the mechanism. The controller parameters can be also determined easily, without any given model parameters. In the present paper, the Continuous Motion NCTF controller for high continuous motion performance is improved in order to enhance the following characteristic of the object motion on NCT and improve the positioning and tracking accuracies of the system. The improved Continuous Motion NCTF controller (referred to as Acceleration Reference-Continuous Motion NCTF controller (AR-CM NCTF controller)) provides the advantages such as the high overshoot reduction characteristics and the low sensitivity disturbance. The AR-CM NCTF controller includes the structure of the Continuous Motion NCTF controller and acceleration reference for the object motion as the additional controller elements. The design procedure of the AR-CM NCTF controller remains easy and practical. In order to confirm the advantages, theAR-CMNCTF controller was examined in positioning and tracking motion performances using the non-contact mechanism. The experimental results prove that the AR-CM NCTF controller achieves the better positioning and tracking performances than the Continuous Motion NCTF controller.